VALIDATION OF DIAGNOSTIC ELEMENTS OF THE NURSING DIAGNOSIS ANXIETY 00146 IN MIDWIFERY - Bubeníková, Štěpánka; Vránová, Věra (Profese Online, 2013)
Aim: The aim of the work was to validate diagnostic elements of the nursing diagnosis Anxiety 00146 by a selected sample of experts-midwives in the Czech Republic, and see which diagnostic elements they consider major and minor.Methods: The study followed Fehring Diagnostic Content Validity Model. A set of experts included 34 midwives from the Czech Republic who received at least 4 points according to the modified Fehring criteria. Experts had bachelor's degree in midwifery or minimal five years of clinical practice. For accessing the significance of diagnostic elements we built a measurement instrument containing 79 items - the diagnostic elements listed in the classification system of NANDA-International.Results: Out of the 79 defining characteristics considered by experts-midwives five characteristics were described as major (score ≥ 0,75): internal restlessness (0,76), increased blood pressure (0,75), tachycardia (0,75), tachypnea (0,75), threats to the status of role in health (0,76).Conclusion: The results of this study indicate that midwives consider only five defining characteristics as major for assesing anxiety of mothers coming to the delivery room for delivery.
Keywords: nursing diagnosis; anxiety; validation; DCV model; expert; midwifery